Rancang bangun mesin sablon cup semi otomatis - Sulis Dri Handono; Mafruddin Mafruddin; Ari Dwi Prasetyo; Bambang Iswadi; Riki Purnomo (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2022)
Screen printing is a technique of printing graphic designs using gauze or called screens. One application of the screen printing machine is on the cup. The more beverage vendors in cup packaging like today, the more screen printing machines are needed. To meet these needs, a cup screen printing machine was made. The purpose of the study was to determine the shape and dimensions as well as the performance of the semi-automatic cup screen printing machine. The research method carried out is by designing and manufacturing a semi-automatic cup screen printing machine and testing with two different types of molding, namely 14 Oz and 16 Oz. From the results of the design and manufacture of the semi-automatic cup screen printing machine design, the length is 600 mm, the width is 400 mm and the height is 900 mm. Using an electric motor of 0.25 HP, gear box 1:60, screen length of 400 mm and width of 150 mm and using a steel frame ST 37 type L. Based on the results of tests and calculations it is known that the production capacity of the screen printing machine is 300 cups/hour and the quality production with 14 Oz molding type is 92% good, 4.67% normal, 2.6% bad while 16 Oz molding is 88% good, 7.34% normal, 4.6% bad. The electrical power consumption of the screen printing machine is 328.6 Watt and the mechanical efficiency is 54.04 %.